Covalently Palladated Oligonucleotides Through Oxidative Addition of Pd-0 - Räisälä H.; Lönnberg T. (WILEY-V C H VERLAG GMBH, 2026)
An 11-mer oligonucleotide incorporating a central (2-iodobenzoylamino)methyl residue has been synthesized and palladated by oxidative addition of Pd-2(dba)(3). UV melting profiles of the duplexes formed by the palladated oligonucleotide with its natural complements were biphasic and the higher melting temperatures (T-m) exhibited considerable hysteresis. CD spectra, in turn, resembled those of canonical B-type double helices. Two-step denaturation, with the "low-T-m"melting involving only canonical base pairs and the "high-T-m" melting involving also dissociation of a Pd-II-mediated base pair, appears the most likely explanation for the observed UV melting profiles. As the latter step in all cases takes place at a higher temperature than denaturation of natural duplexes of the same length, the putative Pd-II-mediated base pairs are stabilizing.